Marketing Promotion Strategy for the Dental and Mouth Special Hospital, Faculty of Dentistry, University of Indonesia in the Adaptation to the New Normal Habits - Paramita, Bunga Listia; Ardiani, Revy; Novolino, Novalino; Lova, Lovia; Sulistiadi, Wahyu (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2022)
Dentists are a profession that has a high risk of contracting Covid-19 in providing dental health services. Concerns about contracting Covid-19 from dentistry are not only felt by dentists, but also by patients. This can be seen from the decline in the number of visits to the Dental and Mouth Special Hospital, Faculty of Dentistry, University of Indonesia (RSKGM FKG UI) since reopening services in June 2020. Therefore, this study aims to analyse the marketing promotion strategy of RSKGM FKG UI during this period, adapting new habits in order to rebuild patient confidence to seek treatment at a dentist without worrying about contracting Covid-19 and still choosing RSKGM FKG UI as their health service provider. This research method is descriptive qualitative with triangulation method techniques. The results of this study state that direct marketing methods to patients, marketing through social media, combination of space, launched a practice management book during the Covid-19 pandemic, and application of health protocols can increase patient visits again during the adaptation period of the new Covid-19 pandemic habits. Keywords: Direct Marketing, Health Protocols, New Habits, Promotion Strategies